Managerial Entrenchment and Capital Structure Decision: A Case of Nepal - Pokharel, Post Raj (NRB Economic Review, 2013)
This paper tests the influence of managerial entrenchment and capital structure decisions using Nepalese firms' data and executives view. A majority of earlier studies show that firm leverage is negatively associated with the degree of entrenchment of managers. This study examines whether or not this is consistent in the context of Nepal. The data were taken from top listed companies on NEPSE, pharmaceuticals companies registered in Department of Drug Administration and other non-listed companies. To achieve the objective of the study, a descriptive and causal comparative research design has been administered. The managerial entrenchment index has been calculated using Principal Component Analysis. The major finding of the study shows that the managerial entrenchment increases as the percentage of CEO ownership rises. There exists positive association of managerial entrenchment and CEO percent ownership which suggests that increase in equity holding by CEO or top executives leads to lower shareholder rights or higher managerial entrenchment.